Analysis of the Constitutional Court's Authority to Change the Age Requirements for Presidential Candidates and Vice Presidential Candidates in the Constitutional Court's Decision Number 90/PUU-XXI/2023 - Darma, Burmansyahtia (NEGREI: Academic Journal of Law and Governance, 2024)
This study analyzes the authority of the Constitutional Court in changing the age requirements for presidential and vice presidential candidates through Decision Number 90/PUU-XXI/2023. The main focus of this research is qualitative research, with a literature study approach which examines a theory or decision to examine the legal basis and authority of the Constitutional Court in conducting a judicial review of the age requirements for presidential and vice presidential candidates in article 169 letter q of Law Number 7 of 2017 concerning General Elections against the 1945 Constitution. The research method used is normative juridical with a legislative and analytical approach. The results of the study show that the Constitutional Court's decision violates the principle of separation of powers and judicial activism.